Estimates of the Prevalence, Intensity and the Number of Workers Exposed to Cigarette Smoking across Occupations and Industries in Korea - Jung, Hyejung (J Korean Med Sci, 2019)
BACKGROUND: Tobacco smoking affects the incidence of various illnesses such as lung cancer, respiratory diseases, and cardiovascular diseases. In an effort to prevent smoking-related cancers, we aimed to estimate the smoking prevalence, intensity, and number of workers exposed to smoking, which would be specific to the occupational and industrial circumstances in Korea. METHODS: We used the Korean Working Condition Survey (KWCS) and Korea's Census data. Smoking prevalence and intensity were estimated using the KWCS data. The number of smokers was estimated by multiplying smoking prevalence with the number of workers in the occupation or industry. Smoking prevalence, intensity, and number of smokers were estimated for major, sub-major, and minor groups of occupation and industry. RESULTS: Of the total labor force in 2010, 52.66% of men and 5.24% of women workers were estimated to be current smokers. Men workers smoked 15.42 cigarettes/day, and women workers 11.29 cigarettes/day. In terms of occupation, “craft and related trades workers” demonstrated the highest smoking prevalence (52.24%). “Managers” smoked the highest number of cigarettes (16.63 cigarettes/day) and “equipment, machine operating, and assembling workers” comprised the largest number of estimated smokers (1,368,726 workers). In terms of industry, “mining and quarrying” had the highest smoking prevalence (69.27%). Those in “construction” smoked the highest number of cigarettes (17.16 cigarettes/day) and those in “manufacturing” comprised the largest number of estimated smokers (1,629,893 workers). CONCLUSION: Our results may help in setting priorities for smoking prevention-related activities. In addition, these results can be used for epidemiological studies controlling for the effect of smoking by occupation or industry.